The regulatory role of pioneer factors during cardiovascular lineage specification – A mini review - Sierra-Pagan, Javier E.; Garry, Daniel J. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) remains the number one cause of death worldwide. Ischemic heart disease contributes to heart failure and has considerable morbidity and mortality. Therefore, alternative therapeutic strategies are urgently needed. One class of epigenetic regulators known as pioneer factors has emerged as an important tool for the development of regenerative therapies for the treatment of CVD. Pioneer factors bind closed chromatin and remodel it to drive lineage specification. Here, we review pioneer factors within the cardiovascular lineage, particularly during development and reprogramming and highlight the implications this field of research has for the future development of cardiac specific regenerative therapies.